Functional polymorphisms of innate immunity receptors are not risk factors for the non‐SBP type bacterial infections in cirrhosis. (17th January 2018) - Dinya, Tamas; Tornai, Tamas; Vitalis, Zsuzsanna; Tornai, Istvan; Balogh, Boglárka; Tornai, David; Antal‐Szalmas, Peter; Sumegi, Andrea; Andrikovics, Hajnalka; Bors, Andras; Tordai, Attila; Papp, Maria
Abstract: Background & Aims: Pattern recognition receptors (PRRs) have a key role in the innate host defense. Functional polymorphisms of various PRRs have been established to contribute to an increased susceptibility to spontaneous bacterial peritonitis (SBP). Their role in the development of cirrhosis‐associated bacterial infections (BI), beyond SBP or progressive disease course related to pathological bacterial translocation (BT) remains unknown. Methods: Three hundred and forty‐nine patients with cirrhosis were genotyped for common NOD2 (R702W, G908R and L1007PfsinsC), TLR2 (−16934T>A), and TLR4 (D299G) variants. Incidence of BIs, decompensating events and liver‐related death were assessed in a 5‐year follow‐up observational study. Pathological BT was assessed based on the presence of antimicrobial antibodies or lipopolysaccharide‐binding protein (LBP) level. Results: In patients with ascites (n = 88) only NOD2 gene variants were associated with an increased cumulative probability of SBP (76.9% ± 19.9%) compared to wild‐type (30.9% ± 6.9%, P LogRank  = .047). Individual or combined PRR genetic profiles were associated with the risk of non‐SBP type BI. Advanced disease stage (HR [95% CI]: 2.11 [1.38‐3.25]) and prior history of a BI episode (HR: 2.42 [1.58‐3.72]) were the major clinical risk factors of a subsequent BI. The risk of a non‐SBP type BI in patients with advanced disease and a prior BI was even higher (HR: 4.74 [2.68‐8.39]). The frequency of antimicrobial antibodies and LBP levels did not differ between various PRR genotypes. Correspondingly, PRR genetic profile was not able to predict the long‐term disease course. Conclusions: In cirrhosis, functional polymorphisms of PRRs did not improve the identification of patients with high risk of BI beyond SBP or progressive diseases course.